2023
DOI: 10.3390/nu15245090
|View full text |Cite
|
Sign up to set email alerts
|

Is Dietary (Food) Supplement Intake Reported in European National Nutrition Surveys?

Eleni Maria Papatesta,
Anastasia Kanellou,
Eleni Peppa
et al.

Abstract: Dietary (food) supplements (DSs) have seen a sharp increase in use and popularity in recent years. Information on DS consumption is vital for national nutrition monitoring. The objective of this study was to investigate whether DS intake was reported in the National Nutrition Surveys (NNSs) in all European countries. NNSs reporting DS use were retrieved via literature review (i.e., PubMed, Google Scholar, Scopus), scientific and organizational publications (EFSA), or open-published government and other officia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
(149 reference statements)
1
0
0
Order By: Relevance
“…Similar to our results, other studies also show a high prevalence of consumption of dietary supplements containing vitamin D, multivitamins, vitamin C, omega-3 fatty acids, probiotics, and zinc [22,23]. In our study, the prevalence of these dietary supplements was observed in the general samples also in the subgroups of respondents with a negative assessment of personal health.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, other studies also show a high prevalence of consumption of dietary supplements containing vitamin D, multivitamins, vitamin C, omega-3 fatty acids, probiotics, and zinc [22,23]. In our study, the prevalence of these dietary supplements was observed in the general samples also in the subgroups of respondents with a negative assessment of personal health.…”
Section: Discussionsupporting
confidence: 91%